2014
DOI: 10.1371/journal.pone.0094006
|View full text |Cite
|
Sign up to set email alerts
|

Screening Primary-Care Patients Forgoing Health Care for Economic Reasons

Abstract: BackgroundGrowing social inequities have made it important for general practitioners to verify if patients can afford treatment and procedures. Incorporating social conditions into clinical decision-making allows general practitioners to address mismatches between patients' health-care needs and financial resources.ObjectivesIdentify a screening question to, indirectly, rule out patients' social risk of forgoing health care for economic reasons, and estimate prevalence of forgoing health care and the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…20 DiPCare-Q, yoksul bireylerin belirlenmesinde geçerli ve güvenilir bir veri toplama aracı olarak birçok çalışmada kullanılmıştır. 23,24 Ancak Boyer ve arkadaşları (2014) internet erişiminin (madde 12) veya sinemaya gitmenin (madde 9) yoksulluğun işareti olmadığını, kişisel tercihi yansıtabileceğini belirtmektedir. 12 Bahsedilen maddelerin DiPCare-Q'da sosyal yoksunluk boyutunda değerlendirildiği ve sosyal yoksunluğun daha önce bahsedilen nedenlerle sağlık çıktıları üzerindeki kanıtlanmış etkisi düşünülürse bu eleştiriyi haklı olarak değerlendirmek mümkün değildir.…”
Section: Discussionunclassified
“…20 DiPCare-Q, yoksul bireylerin belirlenmesinde geçerli ve güvenilir bir veri toplama aracı olarak birçok çalışmada kullanılmıştır. 23,24 Ancak Boyer ve arkadaşları (2014) internet erişiminin (madde 12) veya sinemaya gitmenin (madde 9) yoksulluğun işareti olmadığını, kişisel tercihi yansıtabileceğini belirtmektedir. 12 Bahsedilen maddelerin DiPCare-Q'da sosyal yoksunluk boyutunda değerlendirildiği ve sosyal yoksunluğun daha önce bahsedilen nedenlerle sağlık çıktıları üzerindeki kanıtlanmış etkisi düşünülürse bu eleştiriyi haklı olarak değerlendirmek mümkün değildir.…”
Section: Discussionunclassified
“…These indicate an association between higher rates of forgone care and female gender, younger age, rural living area, unemployment, low educational level, low income and poor health [4,9,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…
Forgoing care because of costs is a frequent situation in many countries, with estimated prevalences going from 4% to 30% [1][2][3][4][5][6]. It can be defined as a decision of not seeking care when needed because of financial reasons and the term is used interchangeably with unmet needs as both terms provide similar information [7].
…”
mentioning
confidence: 99%
“…Whereas most studies on the prevalence of forgoing care because of costs target the general populations, little is known of the prevalence of forgoing care for people with specific chronic conditions. The few studies exploring this issue reported a prevalence close to general population figures [5,[8][9]. As people with chronic conditions have a high demand of health care, such prevalence may either be lower, since they are being followed by a health practitioner and are already navigating the system, or on the contrary, may be similar or higher, since they might decide to prioritize some health issues at the expense of other conditions.…”
mentioning
confidence: 99%